2019
DOI: 10.3390/antiox8100459
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of In Vitro Antioxidant and Antibacterial Potential of Silver Nanoparticles Obtained by Biosynthesis Using Beech Bark Extract

Abstract: Green synthesis is one of the rapid and best ways for silver nanoparticles (AgNP) synthesis. In the present study, synthesis and bioactivity of AgNPs has been demonstrated using water beech (Fagus sylvatica L.) bark extract. The physical and chemical factors such as time, metal ion solution, and pH, which play a vital role in the AgNPs synthesis, were assessed. The AgNPs were characterized by ultraviolet-visible (UV-Vis) spectrometry, Fourier transform infrared spectroscopy (FT-IR), and transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…A thorough comparison between the effects of different sizes and shapes on the final properties usually requires the same characteristics of the natural extract used for phytosynthesis. Tanase et al [34] evaluated the antimicrobial potential of different sized Ag NPs (tuned by varying the synthesis pH) against S. aureus, methicillin-resistant S. aureus, E. coli, K. pneumoniae, and P. aeruginosa. In all cases, the the MIC and MBC (minimum bactericidal concentration) were significantly lower for the smaller dimension NPs.…”
Section: Recent Findings In the Morphology-properties Correlationmentioning
confidence: 99%
“…A thorough comparison between the effects of different sizes and shapes on the final properties usually requires the same characteristics of the natural extract used for phytosynthesis. Tanase et al [34] evaluated the antimicrobial potential of different sized Ag NPs (tuned by varying the synthesis pH) against S. aureus, methicillin-resistant S. aureus, E. coli, K. pneumoniae, and P. aeruginosa. In all cases, the the MIC and MBC (minimum bactericidal concentration) were significantly lower for the smaller dimension NPs.…”
Section: Recent Findings In the Morphology-properties Correlationmentioning
confidence: 99%
“…Based on the literature data, the main objectives of the current study are: Biosynthesis of AgNPs using polyphenolic spruce bark extract (SBE), with a previously developed technique [14,15]; the determination of the influence of different factors on the biosynthesis processes (metallic salt, time and pH); the characterization of biosynthesized AgNPs by specific assays: Ultraviolet-Visible Spectrometry (UV-Vis), Fourier transforms infrared spectroscopy (FTIR), and Transmission Electron Microscopy (TEM); and the evaluation of antioxidant and antibacterial activity for biosynthesized AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…In the timber industry, bark is considered a waste product used for combustion and as garden mulch. Some studies have developed a different process to remove valuable biocompounds from bark in order to produce high-tech, valuable materials [9,10,11]. The bark of woody vascular plants play important roles in plant protection because of their content of bioactive compounds with antimicrobial effects [12].…”
Section: The Bark Of Woody Vascular Plants—a Source Of Phytoconstimentioning
confidence: 99%
“…The bark of woody vascular plants play important roles in plant protection because of their content of bioactive compounds with antimicrobial effects [12]. In a recent study, it was found that bark extracts may be a good source of reducing agents in synthesized metallic NPs [9].…”
Section: The Bark Of Woody Vascular Plants—a Source Of Phytoconstimentioning
confidence: 99%